SELF CONCEPT ADOLESCENCE OF EXPERIENCING BULLYING IN JUNIOR HIGH SCHOOL - Trihadi, Dayat; Laela, Fatchul; Pratiwi, Apriliani (Jurnal Ners Widya Husada, 2020)
In Many Junior High School Purwokerto there are many victims of bullying, cases of bullying in schools, among others, mocked, things were in hiding, fighting, attack, asking for money by force and the provision of threat. Oppressive measures has caused one of our students the opportunity to decide to move school. To describe Self Concept Adolescence Of  Experiencing Bullying At Junior High School in Purwokerto. This type of research that is used is descriptive of a qualitative with with the phenomenology to the number of participants as much as Seven student and data processing with MAXQDA the 2018. The concept of the victim of bullying : 1) The description of four participants who received comments are feeling low, inferior and withdrawn, and three participants don't feel embarrassed, inferior and withdrawn from the environment. 2) The participants recognize his identity, aware of the nature, a new look in to see the advantages and disadvantages of his own, and, confident in expressing its advantages. 3) the role of participants yaiu menikuti the curricular, the role of dikeluarga, a role in the neighborhood. 4) Self ideal, 3 participants can not interact with the social environment and restrict themselves to interact with their peers, and four participants even experience bullying don't shut off from the environment and interact. 5) The participants can meet the ideal itself so it can reach his pride and feeling accepted, the sense of being able, and precious feelings.